Sympathetic Blocks Provided Sustained Pain Relief in a Patient with Refractory Painful Diabetic Neuropathy. (6th February 2012) - Cheng, Jianguo; Daftari, Anuj; Zhou, Lan
Abstract : The sympathetic nervous system has been implicated in pain associated with painful diabetic neuropathy. However, therapeutic intervention targeted at the sympathetic nervous system has not been established. We thus tested the hypothesis that sympathetic nerve blocks significantly reduce pain in a patient with painful diabetic neuropathy who has failed multiple pharmacological treatments. The diagnosis of small fiber sensory neuropathy was based on clinical presentations and confirmed by skin biopsies. A series of 9 lumbar sympathetic blocks over a 26-month period provided sustained pain relief in his legs. Additional thoracic paravertebral blocks further provided control of the pain in the trunk which can occasionally be seen in severe diabetic neuropathy cases, consequent to extensive involvement of the intercostal nerves. These blocks provided sustained and significant pain relief and improvement of quality of life over a period of more than two years. We thus provided the first clinical evidence supporting the notion that sympathetic nervous system plays a critical role in painful diabetic neuropathy and sympathetic blocks can be an effective management modality of painful diabetic neuropathy. We concluded that the sympathetic nervous system is a valuable therapeutic target of pharmacological and interventional modalities of treatments in painful diabetic neuropathy patients.